Diminished vagal activity and blunted diurnal variation of heart rate dynamics in posttraumatic stress disorder. (May 2013) - Agorastos, Agorastos; Boel, Judith A.; Heppner, Pia S.; Hager, Torben; Moeller-Bertram, Tobias; Haji, Uzair; Motazedi, Arame; Yanagi, Matthew A.; Baker, Dewleen G.; Stiedl, Oliver
<x xml:space="preserve">Abstract</x> Affected autonomic heart regulation is implicated in the pathophysiology of cardiovascular diseases and is associated with posttraumatic stress disorder (PTSD). However, although sympathetic hyperactivation has been repeatedly shown in PTSD, research has neglected parasympathetic function. The objective of this study is the long-term assessment of heart rate (HR) dynamics and its diurnal changes as an index of autonomic imbalance in PTSD. Since tonic parasympathetic activity underlies long-range correlation of heartbeat interval fluctuations in the healthy state, we included nonlinear (unifractal) analysis as an important and sensitive readout to assess functional alterations. We conducted electrocardiogram recordings over a 24-h period in 15 deployed male subjects with moderate to high levels of combat exposure (PTSD: n = 7; combat controls: n = 8) in the supine position. HR dynamics were assessed in two 5-h sub-epochs in the time and frequency domains, and by nonlinear analysis based on detrended fluctuation analysis. Psychiatric symptoms were assessed using structured interviews, including the Clinician Administered PTSD Scale. Subjects with PTSD showed significantly higher baseline HR, higher LF/HF ratio in the frequency domain, blunted differences between day and night-time measures, as well as a higher scaling coefficient αfast during the day, indicating diminished tonic parasympathetic activity. Diminished diurnal differences and blunted tonic parasympathetic activity altering HR dynamics suggest central neuroautonomic dysregulation that could represent a possible link to increased cardiovascular disease in PTSD.